The frequency and distribution of healthcare-associated infections in children - Murni, Indah Kartika; Wirawan, Muhammad Taufik; Patmasari, Linda; Laksanawati, Ida Safitri (Paediatrica Indonesiana, 2025)
Background Healthcare-associated infections (HAIs) are major contributors to increased morbidity, mortality, and healthcare costs. Ongoing epidemiological surveillance of nosocomial infection is needed to accurately assess their burden and inform prevention strategies. Objective To determine the frequency and distribution of HAIs. Methods A 26-month prospective cohort study (February 2016 to April 2018) was carried out at Dr Sardjito Hospital, a tertiary hospital in Indonesia, where pediatric patients hospitalized in the wards and pediatric ICU were monitored daily. HAIs were defined according to the criteria set by the Centers for Disease Control and Prevention. Results Out of 1,855 patients enrolled in the study period, 314 (16.9%) had HAI with an incidence density rate of 20.1 infections per 1,000 patient-days (416/20,672). The incidence of nosocomial urinary tract infection (UTI) was 4.3% (82/1,855) and the catheter-associated urinary tract infection (CAUTI) incidence density rate was 16.5 CAUTIs/1,000 patient-days (36/2,179). The incidence of nosocomial pneumonia, which includes both hospital-acquired pneumonia (HAP) and ventilator-associated pneumonia (VAP), was 3.2% (59/1,885), while the specific incidence rate of VAP was 5.1 per 1,000 patient-days (14/1,359). The incidence of nosocomial bloodstream infection was 1.9% (36/1,855) and the central line-associated bloodstream infection (CLABSI) incidence rate was 4.4 CLABSIs/1,000 patient-days (5/1,121). The incidences of surgical site infection, phlebitis, nosocomial upper respiratory infection, and nosocomial gastroenteritis were 0.2% (3/1,855), 0.9% (17/1,855), 2.9% (54/1,855), and 3.4% (63/1,855), respectively. Conclusion One-sixth of children in our hospital developed HAIs, with an incidence rate of 20.1 HAI/1,000 days. The most common HAI was CAUTI, followed by VAP and CLABSI.